Bali dalam Dilema Pariwisata dan Budaya - I Gede Sutarya (UHN IGB Sugriwa Denpasar, 2017)
Tourism-culture relationships are expected to become mutual relations since Bali tourism was declared by the colonial government in the 1920s. In the case of Bali tourism, relationships do not always run in sync. Tourism and culture often clash, beginning with the conflict holyland of Tanah Lot Temple in 1994, the National Tourism Strategic Area (KSPN) Besakih in 2011, and the reclamation of Teluk Benoa in 2016. The roots of tourism and culture in Bali become a problem to be dissected for the purpose of revealing the root of the problem, analyzing the historical relationships at the root of the problem, and formulating solutions for the development of Balinesetourism in tune with Balinese culture. An overview of this issue can be explained that tourism and cultural conflicts arose when the planned mass tourism of 1971 began to exceed the target of foreign tourists in 1994. The root of the problem is the stampede of Balinese holiness. The stampede of the local value of Bali is causing antipathy towards the development of Bali tourism.Therefore, the development of Bali tourism must make restrictions on the visits of foreign tourists to provide an opportunity to local people to plan their own tourism Bali fair.